1999
DOI: 10.2307/3345719
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tone-Quality Changes on Intonation and Tone-Quality Ratings of High School and College Instrumentalists

Abstract: We investigated the effects of variations in tone quality on listeners' perception of both tone quality and intonation. University music and nonmusic major instrumentalists and high school students participating in instrumental ensembles served as listeners (N = 116). High-quality digital samples of clarinet, trumpet, and trombone tones were used. The original tone quality of each instrument was manipulated to produce experimental stimuli of "bright" and "dark" relative to the unaltered tone quality. Results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 14 publications
2
35
1
Order By: Relevance
“…One of the reasons that intonation is a challenging concept for developing musicians is that pitch and timbre have been shown to be mutually related (Feldman et al, 2016). In fact, researchers have previously reported that listeners mistook intonation for tone quality when they rated bright timbres as sharper in pitch and dark timbres as flatter in pitch (Geringer & Worthy, 1999; Wapnick & Freeman, 1980). Additionally, wind instrumentalists performed sharper when attempting to match bright-timbre stimuli and flatter when trying to match dark-timbre stimuli (Worthy, 2000).…”
Section: Pitch Versus Timbrementioning
confidence: 99%
See 1 more Smart Citation
“…One of the reasons that intonation is a challenging concept for developing musicians is that pitch and timbre have been shown to be mutually related (Feldman et al, 2016). In fact, researchers have previously reported that listeners mistook intonation for tone quality when they rated bright timbres as sharper in pitch and dark timbres as flatter in pitch (Geringer & Worthy, 1999; Wapnick & Freeman, 1980). Additionally, wind instrumentalists performed sharper when attempting to match bright-timbre stimuli and flatter when trying to match dark-timbre stimuli (Worthy, 2000).…”
Section: Pitch Versus Timbrementioning
confidence: 99%
“…Based on those studies, band directors should be aware of the potential for pitch-timbre confusion among their students (Geringer & Worthy, 1999; Wapnick & Freeman, 1980; Worthy, 2000) and evaluate the effects of timbral instructions to make certain that desired timbre changes do not unintentionally result in pitch changes (Springer et al, in press). When discussing relationships between pitch and timbre, aural models will likely be more effective than verbal instructions alone.…”
Section: Pitch Versus Timbrementioning
confidence: 99%
“…245-6). The just noticeable difference studies in human pitch perception suggest that a singer will be unable to detect an error that is within a range of 5 to 25 cents depending on test conditions, pitch, and level of musical experience (Burns, 1999;Burns & Campbell, 1994;Burns & Ward, 1978;Geringer & Worthy, 1999;Houtsma, 1968;McDermott, Keebler, Micheyl, & Oxenham, 2010;Warrier & Zatorre, 2002;Zarate, Ritson, & Poeppel, 2012). This would lead one to expect a probability distribution spanning both sides of this radius based only on auditory perception.…”
Section: Tonic Tonementioning
confidence: 99%
“…Musicians (at least well-studied Western musicians) are sensitive to the structure of musical figures even when they are transposed, reflecting invariance and generalization across keys (Tervaniemi, Rytko¨nen, Schro¨ger, Ilmoniemi, & Na¨a¨ta¨nen, 2001). As with lexical tone, spectral (timbre) information aids in pitch perception, and this is subject to experience: more experienced musicians less likely to conflate timbre and tuning (Geringer & Worthy, 1999), and they perform better at intonation tasks in the timbre of their own (more familiar) instruments (Pantev, Roberts, Schulz, Engelien, & Ross, 2001;Pantev et al, 2003).…”
Section: Musical Normalizationmentioning
confidence: 99%